PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN SKEE BERBASIS ANDROID DENGAN ADOBE FLASH CS6 KELAS XI TOI DI SMK NEGERI 7 PEKANBARU: PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF - Rilva, Maulana2001; Fauzan Azim; Khairul Anshari; Zuqriva Hayati (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2024)
The research and development carried out is in the form learning media . Android based with Adob Flash CS6 on control system subject. Electronic eletromechanics on the subject of electrical control system components. Research is packaged and developed using the research and development or R&D method form several stages that follow ADDIE, including the analysis stage, product design, product development, product testing, and final product revision. According to experts, the feasibility of Andorid-based learning media with Adobe Flash CS6 in the subject of electronic elektromecanical control system is very feasible. The validation result experts got a percentage score of 90%. Media experts got a percentage score of a 72%. Overall, result of questionnaire recapitulation. At the validation stage, the product has very appropriate criteria. Teacher and student responses. Regarding the attaractiveness of Android based learning media with Adobe Flash CS6 in the subject of electronic electromechanical control system wich is very interesting. The result of the teacher trials got a percentage score of 91%. The result of small group trials got a score of 97% and the field trials got a percentage score of a 91%. All questionnaire recapitulation result at the product trial stage have very interesting criteria.